2023
DOI: 10.1038/s41598-023-31729-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing earthquake preparedness knowledge and practice among Nepalese immigrants residing in Japan

Abstract: This study aims at increasing earthquake preparedness knowledge perception and practice among Nepalese immigrants residing in Japan through an educational intervention. A single arm quasi experimental study was conducted among Nepalese immigrants residing in Japan. An educational intervention was prepared along with a 52 itemed questionnaire. In total, 165 participants responded to our questionnaire. Majority of them were male (67.88%), and the mean age was 32.78 years. Generalized equation model showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Types and methods of disaster preparedness education and training programs developed for adults found based on 10 articles that have been extracted using modern methods, namely Virtual Reality (VR), Immersive Virtual Reality (IVR) and Serious Games (SG) , and S&G ( Simulation and Gaming ) . Education and training programs also still use traditional methods , namely reading manuals, earthquake safe house video games, lectures, debriefing and group discussions, providing modules, training and workshops using pamphlets, books and CDs, campaigns, posters, animated films, and live demonstration ( Li et al, (2017) ; Feng et al, (2020) ; Gampell et al, (2021) ; Toyoda, (2020) ; Amini et al, (2021) ; Bhandari et al , (2023) ; Arulmohi et al, (2017) ; Jouhari et al, (2015) ; Gesser-Edelsburg et al, (2021) ; ). Types and methods in education and training consist of several materials that support improving community preparedness related to disasters due to natural earthquakes…”
Section: Program Types and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Types and methods of disaster preparedness education and training programs developed for adults found based on 10 articles that have been extracted using modern methods, namely Virtual Reality (VR), Immersive Virtual Reality (IVR) and Serious Games (SG) , and S&G ( Simulation and Gaming ) . Education and training programs also still use traditional methods , namely reading manuals, earthquake safe house video games, lectures, debriefing and group discussions, providing modules, training and workshops using pamphlets, books and CDs, campaigns, posters, animated films, and live demonstration ( Li et al, (2017) ; Feng et al, (2020) ; Gampell et al, (2021) ; Toyoda, (2020) ; Amini et al, (2021) ; Bhandari et al , (2023) ; Arulmohi et al, (2017) ; Jouhari et al, (2015) ; Gesser-Edelsburg et al, (2021) ; ). Types and methods in education and training consist of several materials that support improving community preparedness related to disasters due to natural earthquakes…”
Section: Program Types and Methodsmentioning
confidence: 99%
“…The materials in the education and training program for disaster preparedness due to natural earthquake events provided to the community are based on the Health Belief Model (HMB) (Amini et al, 2021). The materials provided in education and training are divided into three major parts, namely: (1) Disasters due to earthquake events in general: factors affecting the strength of earthquakes, building strength, location, distance from the sea, soil type, earthquake magnitude, and earthquake preparedness, providing food and drink, conducting routine exercises with household members, moving objects hanging on the wall, and looking for various sources of earthquake forecast information (Gesser-Edelsburg et al, 2021), (2) Disaster management due to earthquake natural events: things to pay attention to before, during, and after an earthquake, what not to do during an earthquake, how to drop cover and hold during an earthquake, early warning to use, emergency contact numbers, some important websites to get earthquake information and so on (Bhandari et al, 2023). Securing furniture, providing food and water, finding designated evacuation centers, preparing emergency equipment, discussing disaster planning with family members, seeking help from neighborhood residents and vice versa in times of disaster (Arulmohi et al, 2017).…”
Section: Program Materialsmentioning
confidence: 99%
“…There has been an increase in earthquake preparedness literature recently, according to Bhandari et al (2023) there are various lists of who needs to be prepared, what needs to be prepared, and how it should be done. For people throughout the world, disaster preparedness can mean different things.…”
Section: Earthquake Preparednessmentioning
confidence: 99%
“…People should be prepared for catastrophes by what/who is anticipated to be pretentious in various areas of cities and nations, as noted by Ward (2020). Numerous studies measuring earthquake readiness have indicated that many individuals are not prepared for the effects of natural disasters (Spittal, 2003;Karanci et al 2012;Momani and Salmi, 2012;Hemond and Robert, 2012;Norman et al, 2012;Oral et al, 2015;Bhandari et al, 2023).…”
Section: Earthquake Preparednessmentioning
confidence: 99%
See 1 more Smart Citation